The Color of School Reform : Race, Politics, and the Challenge of Urban Education - Henig, Jeffrey R., 1951- (Book collections on Project MUSE., 2001)
Why is it so difficult to design and implement fundamental educational reform in large city schools in spite of broad popular support for change? How does the politics of race complicate the challenge of building and sustaining coalitions for improving urban schools? These questions have provoked a great deal of theorizing, but this is the first book to explore the issues on the basis of extensive, solid evidence. Here a group of political scientists examines education reform in Atlanta, Baltimore, Detroit, and Washington, D.C., where local governmental authority has passed from white to black.